Study, Design and Construction of an Early Warning Environmental Radiation Monitoring Station - Thieu, Dang Quang; Toan, Tran Ngoc; My, Nguyen Thi Bao; Sy, Nguyen Van; Tien, Vu Van; Mai, Nguyen Thi Thuy; Cuong, Le Dinh (Communications in Physics, 2013)
We report on the design and construction of an Early Warning Environmental Radiation Monitoring Station (EWERMS), used ONLINE in the environmental radiation monitoring and early warning network. It has a high sensitivity and can send a prompt alarm signal via Internet to the emergency management office. It includes four gamma probes: one NaI(Tl) and three Geiger Mueller (GM) detectors. The NaI(TL) detector is used to monitor spectrum environmental radiation and measure the isotopic composition, the GM detectors are used to detect and measure high gamma ray rates. The instrument has been designed to be used outdoor and tolerate large and rapid temperature variations. The photomultiplier tubes (PMT), amplifiers and Analog To Digital (ADC) gains are stabilized using pulsed LEDs as precision reference light sources.